AN ANALYSIS OF THE UNNARRATABLE IN FAE MYENNE NG’S BONE - Sufen Wu (Sanata Dharma University, 2022)
Bone, a novel written by Chinese American novelist Fae Myenne Ng, is concerned with the fictional history of a family of Chinese immigrants who live in the Chinatown of San Francisco from the 1960’s to 1990’s. In Bone, Ng not only does a good job in speaking out the difficulties and hardships the immigrants encounter on the new soil but also hides some information beneath the surface, leaving it unnarrated, like Ona’s inner activities and Mah’s adultery and the Chinese Exclusion Law. Therefore, this study, drawing on the theory of the unnarratable put forward by Warhol, aims to study the supranarratable, the antinarratable, and the paranarratable, three categories of the unnarratable, so as to discover the connection between the author’s intentions with the text and to fumble out the hidden plot within Ng’s Bone. Only when we find out the unnarrated and combine it with the narrated can we better understand the Chinese Americans’ stories and their unspeakable bone-piercing pain.